Analysis of Participation in the Management of BOS funds in the RKAS Program to Improve Accountability, Transparency and School Welfare: Analisis Partisipasi Pengelolaan Dana Bos dalam Program RKAS untuk Meningkatkan Akuntabilitas, Transparansi, dan Kesejahteraan Sekolah - Ajeng Wulan Ayu Sari; Wiwit Hariyanto (Academia Open, 2021)
This study discusses the analysis of participation in the management of BOS funds in the RKAS program to improve accountability, transparency and school welfare. With the case of embezzlement of BOS funds and inefficient management, schools must strive for accountability and transparency to account for the entire BOS budget by applying the principle of participation so as to create prosperous schools. The purpose of this study is to find out how to increase accountability, transparency and school welfare in the management of BOS funds in the RKAS program after the participation principle. This study uses qualitative research methods where data collection is obtained from interviews, observations and documentation.The data analysis in this research is data reduction. The results show that participation can increase accountability, transparency and school welfare in the management of BOS funds in the RKAS program, with the participation of the principles of accountability and transparency it can increase, where accountability and transparency of BOS funds in the RKAS program can run well.